Assessment of the efficacy of routine vaccination on the magnitude of Foot and Mouth Disease outbreak in Kafrelsheikh governorate, Delta Region, Egypt - AL-HOSARY, A. A.; EL-TANOBY, A.; OREIBY, A. F.; HEGAZY, Y. M.; KHALEEL ABD-ELGHAFFAR, S. (Journal of the Hellenic Veterinary Medical Society, 2019)
Foot and mouth disease (FMD) is a highly contagious viral disease causes a serious economic impact on livestock production and trading. FMD is an endemic disease in Egypt and a national control program that depends on routine obligatory vaccination of all ruminant species is being followed for disease control. A nation-wide epidemic of FMD was commenced in early 2015 and typical clinical signs of the disease were observed even in vaccinated animals. The morbidity and case fatality rates were high enough to be investigated. In the current study, non-vaccinated and vaccinated animals of different sex and ages were examined to evaluate the efficacy of FMD different vaccines used in Egypt. Clinical, post-mortem and serological examinations were used to confirm the infection, while the molecular investigation was applied to identify the serotype responsible for this epidemic. The incidence rate and the attributable proportion (fraction) of FMD cases which could be avoided by vaccination and vaccine efficacy were calculated. The obtained results confirmed the infection with FMD virus (FMDV) serotype O in both non-vaccinated and vaccinated animals. The incidence of FMD was 86.67% among non-vaccinated animals, while it was ranged from 15% to 31.8% among vaccinated animals according to the type of vaccine used. The attributable fraction was 73.9% and the efficacy of the three used vaccines was 63.3%, 76.92% and 82.25% for Tri-Aphthovac, VSVRI and Meriel vaccines, respectively. In conclusion, vaccination in Egypt is able to minimize the magnitude of outbreaks caused by the same serotype found in the vaccine but was not able to prevent the infection and eliminate the disease. The highest vaccination efficacy was found in Mid-aged animals and male cattle.